The llama (Lama glama) growth hormone gene: Sequence, organization and SNP identification - Daverio, Maria Silvana (2012)
Growth hormone (GH) is a peptide hormone found in most vertebrates, which has important effects on the muscular development during growth as well as on the production and composition of milk during lactation. Here, we report the sequence and organization of the GH gene, its promoter region and several single nucleotide polymorphisms (SNPs) in the llama (Lama glama), a domestic camelid from South America. Like in other mammals, the GH gene in the llama is organized in five exons separated by four introns. Comparison of its coding sequence with that of other cetartiodactyl species showed identities that ranged from 90.3% when compared with that of sheep to 99.1% when compared with that of camel (Camelus dromedarius). Introns were less conserved, particularly Intron C, which in the llama was found to be considerably shorter than in other species. In the promoter region, the TATA box showed a T/C substitution in the first base, also present in the camel. Other regulatory elements of the promoter region are fully conserved, except Sp1, CRE, and the proximal Pit-1 element, which present substitutions with respect to other cetartiodactyl species. Sequencing of the GH gene in a sample of 10 llamas allowed us to identify 15 SNPs, mainly located in non-coding regions. However, three of them were found in the promoter and the 5'-UTR of Exon 1, regions involved in transcription and translation processes. Moreover, in other species, intronic polymorphisms were found to be associated with growth and carcass traits. Therefore, further studies in llama herds will be necessary to infer the role of the polymorphisms found in this paper. © 2011 Elsevier B.V.